Diagnosis and Management of Addiction and Other Mental Disorders (Dual Disorders) - Adan, Ana; Torrens, Marta (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes a compilation of papers published in 2020 and 2021 focused on dual disorders, which are found in significant and growing numbers in both substance addiction and mental health clinics. These contributions assume a broad perspective ranging from exposure to genetic and neurobiological elements to factors such as personality and quality of life. In all cases, these papers aimed to be transferred to and to benefit clinical practice.